Gaza’s reconstruction or Gaza’s redevelopment? - Kubursi, Atif; De Lucia, Caterina; Borri, Dino (Plurimondi, 2025)
This paper reconsiders post-war recovery strategies for the Gaza Strip, arguing that a narrow focus on “reconstruction” is insufficient to address the territory’s structural economic fragilities. It advances a broader framework of “redevelopment,” grounded in the observation that Gaza’s pre-war socio-economic conditions were shaped by long-standing constraints, market fragmentation, and limited policy space. Drawing on Amartya Sen’s conception of development as freedom, the analysis links sustainable recovery to the expansion of economic and institutional capabilities. The paper examines the limits of standard growth models in contexts of severe destruction of physical and human capital and outlines a redevelopment approach aligned with the UN Sustainable Development Goals, with particular emphasis on health, education, and human capital formation. It concludes that while external assistance is an important component of recovery, long-term stability and development depend on addressing the structural conditions that have historically undermined Gaza’s productive capacity.